BELUM EFEKTIFNYA IMPLEMENTASI PROGRAM KESEHATAN GRATIS DI KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Tri Wibowo E.42008070 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This  writing is  meant  to  know factors causing free  Medicare implementation in  Kecamatan Sukadana, Kabupaten Kayong Utara not yet is effective. Background of this research is degree of health of society Kecamatan Sukadana which still lower and quality of service of free health in Kecamatan Sukadana  still  lower.  Formula  problems  of  this  research  is  why  free  Medicare  implementation in Kecamatan Sukadana, Kabupaten Kayong Utara not yet is effective. Intention of this research is to analyse factors causing free Medicare implementation in Kecamatan Sukadana, Kabupaten Kayong Utara not yet is effective.Pursuant to  result  of  research obtained  by conclusion that  factors causing free  Medicare in Kecamatan Sukadana, Kabupaten Kayong Utara not yet effective for example : a) Factor communications in the form of socialization still not yet is effective; b) Factor human resource and appliance resource which still less; c) Factor disposition which still less professional ( owning membership); d) Structure factor bureaucracy not yet walked optimal and effective.Suggestion referring to result of this research is expected to Government Of Kabupaten KayongUtara to more is improving of socialization, doing hygienist and recruitment, paying attention officer incentive level and hygienist, and repairing accomplishment of conditions of service of free Medicare and Card of JAMKESDA. Keyword : effectiveness, implementation, program, free health.